Peningkatan Kompetensi Guru Dalam Pengembangan Silabus dan RPP Dengan Pendekatan Kooperatif - Nasrin Nasrin (JURNAL GLOBAL EDUKASI, 2018)
Abstract: The purpose of this school action research is to improve teacher competence in developing syllabus and learning implementation plan (RPP) and to know how far professional coaching with cooperative approach can improve teacher competence. Ability to be improved is the ability of teachers in developing syllabus and RPP. The subject of the research is the teacher of the entire class who are in SD Negeri 050756 Alur Dua sub distrcit Sei Lepan distrcit Langkat. The result of the research shows that there is an increase of teacher competence in the development of syllabus and RPP is increased from the average value from 48.79 with the criteria of less value at the initial condition, to 69,96 criteria of value enough in the first cycle and become 91,34 criteria of excellent value in the second cycle, with a classical average of 70.03 with good value criteria. The conclusion is professional coaching with cooperative approach can improve teacher competence in SD Negeri 050756 Alur Dua sub distrcit Sei Lepan distrcit Langkat. Keyword: coaching, cooperative, competence, syllabus, learning implementation plan Abstrak: Tujuan dari penelitian tindakan sekolah ini untuk meningkatkan kompetensi guru dalam mengembangkan silabus dan rencana pelaksanaan pembelajaran (RPP) serta mengetahui sejauh mana pembinaan profesional dengan pendekatan kooperatif dapat meningkatkan kompetensi guru. Kemampuan yang akan ditingkatkan adalah kemampuan guru dalam mengembangkan silabus dan RPP. Subjek penelitian adalah guru seluruh kelas yang berada di SD Negeri 050756 Alur Dua kec. Sei Lepan kab. Langkat. Hasil penelitian menunjukkan adanya peningkatan kompetensi guru dalam pengembangan silabus dan RPP meningkat yakni dari nilai rata-rata dari 48,79 dengan kriteria nilai kurang pada kondisi awal, menjadi 69,96 kriteria nilai cukup pada siklus pertama dan menjadi 91,34 kriteria nilai sangat baik pada siklus kedua, dengan rata-rata klasikal sebesar 70,03 dengan kriteria nilai baik. Kesimpulannya adalah pembinaan profesional dengan pendekatan kooperatif dapat meningkatkan kompetensi guru di SD Negeri 050756 Alur Dua kec. Sei Lepan kabupaten Langkat. Kata kunci: pembinaan, kooperatif, kompetensi, silabus, RPP